The Urgency of Education as a Human Investment in Improving the Quality of Education at SMP Negeri 8 Langsa City - Arwinsyah, Diki (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
This article's topic is centered on elements of basic education that can enhance the human development index's quality. The significance of discussing is connected to investing in education or using it as a major source of capital to achieve a country's development objectives. The discussion in this article has led to a classification of the four characteristics of students, educators, education staff, and parents or the community as human resources as investment capital in education at SMP Negeri 8 Langsa. Government support still holds a disproportionate amount of the investment in education funding in SMP Negeri eight Langsa. The return on investment in education, in the form of graduates, can rise even further, enhancing peoples' quality of life. At SMP Negeri 8 Langsa, the use of human resources as educational investment capital is divided into four categories. Aspects relating to students, teachers, employees, parents, or the community. Based on the school's potential, these four elements serve as the total capital for implementing, growing, and improving the quality of education